2023
DOI: 10.1002/gps.5876
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of multiple voices to inform aftercare services for older persons following self‐harm

Abstract: Objectives: Self-harm and suicide are closely related in older adults, highlighting the opportunity for Aftercare interventions in targeted suicide prevention. The study aims were to explore strengths and shortfalls of current Aftercare services for older adults from the perspective of key stakeholders and researchers; and inform a set of guiding principles for older persons' Aftercare.Methods: Semi-structured interviews were undertaken with a convenience sample of older people with lived experience of self-ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
(131 reference statements)
1
0
0
Order By: Relevance
“…Research suggests that healthcare practitioners experience difficulties in recognising self‐harm and mental health problems such as depression, often due to ageism 21 . Similar to findings from this research, previous qualitative research conducted in Australia found that ageism, limited services, funding, and training, often preclude offering of better support for older adults who self‐harm 33 …”
Section: Discussionsupporting
confidence: 72%
“…Research suggests that healthcare practitioners experience difficulties in recognising self‐harm and mental health problems such as depression, often due to ageism 21 . Similar to findings from this research, previous qualitative research conducted in Australia found that ageism, limited services, funding, and training, often preclude offering of better support for older adults who self‐harm 33 …”
Section: Discussionsupporting
confidence: 72%